PERAN PEMUDA KAMPUNG LALI GADGET DALAM MENGENALKAN PERMAINAN TRADISIONAL SEBAGAI WUJUD SIKAP CINTA TANAH AIR PADA ANAK USIA DINI DI DESA PAGAR NGUMBUK KECAMATAN WONOAYU KABUPATEN SIDOARJO - Siti Fajri Novi Astuti; Listyaningsih Listyaningsih (Kajian Moral dan Kewarganegaraan, 2022)
Abstract This study aims to describe the role of village youth in introducing gadgets to traditional games as a form of love for the homeland in early childhood in Pagar Ngumbuk Village, Wonoayu District, Sidoarjo Regency. In this study using qualitative research methods with descriptive research types with the main informants of the study, namely the founder of the Lali Gadget Village and the core administrators of the Lali Gadget Village such as the secretary, treasurer, operational division, and equipment division. Data collection techniques used in this study are observation, interviews, and documentation, as well as data analysis used in this study, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study are the role of the youth of the village of Lali gadgets in introducing traditional games as a form of love for the homeland in early childhood, namely by introducing various types of traditional games and explaining the benefits of these traditional games, holding several routine activities and some of these activities focusing on traditional games, then provide assistance to children when playing and when making games, so that these things can foster an attitude of love for the homeland in early childhood through traditional games. In addition, to realize an attitude of love for the homeland in early childhood, it can be done through ways, namely by fostering an attitude of mutual cooperation, then Lali Gadget Village also makes various facilities and infrastructure as a means of supporting various activities carried out in Kampung Lali Gadget. Keywords: Role, Traditional games, Love for motherland